Probabilistic method to determine the overall rock block failure based on failure mode - Hongze ZHAO; Zequan LI; Chi Seng KONG (Engineering Transactions, 2016)
In rock slopes or underground excavations, due to the structure of the cutting surface, rock typically exhibits strong random properties, such as the structure of the surface geometry and mechanical parameters showed strong randomness, resulting in a high degree of rock mass uncertainty of the previous studies. In this paper, a new approach to estimating probability of failure of a rock block is proposed. Based on the previous studies investigating the potential failure of the block theory model, the block failure calculation took into account the geometrically formed probability, failure mode, and mechanical failure probability. As an engineering application of the presented model, the analysis of block failure, observed in a copper mine site in Australia, was performed. The Monte-Carlo simulation method was used for the evaluation where plane roughness, friction angle, and cohesion were considered as random variables. The results of this example show that the model can be used as a basis for evaluating the reliability of the block.